The development of an android-based English tenses learning application for Fakfak State Polytechnic - Magfirah, Titing; Arridha, Riyadh; Fachruddin, Muh.; Rahmi, Wa; Manistasyaroh, Manistasyaroh (Jurnal Mantik, 2024)
Currently, English has become a global language and almost every level of education studies English. One of the materials is grammar. Good grammar mastery can be used to communicate in English, writing letters, messages, and scientific writing. One of the materials in mastering grammar is Tenses. Tenses is a sentence pattern that is arranged based on the words to be created. However, tenses are considered difficult and quite boring to learn for some students at the Fakfak State Polytechnic, West Papua. To make it easier to learn tenses is the use of mobile learning to help users in learning something and it can be accessed easily. This research aims to develop an Android-based English Tenses learning application for students at the Fakfak State Polytechnic, West Papua. The method used in this research is the Waterfall method, where a software development model is carried out sequentially where one stage is carried out after the previous stage has been completed. The black box testing results show that the application can work well. Meanwhile the questionnaire result about application performance revealed that 91% of respondents strongly agreed that with this application become an effective way to increase student motivation in learning English Tenses